Effects of exogenous sulfate on the chromium(VI) metabolism of chromium(VI)-resistant engineered strains - Xinglong Li (Elsevier, 2021)
Objective: To explore the effects of exogenous sulfate on the efficiency of chromium(VI) metabolism of three chromium(VI)-resistant Escherichia coli strains (eChrA / eChrB / eChrAB) by adding chromium(VI)-resistance genes chrA and/or chrB, for better understanding and further application of these Cr(VI)-resistant strains in environmental and industrial chromium removal. Methods: Based on three engineered Cr(VI)-resistant strains exposed to different concentrations of sulfate: i) Evaluation of Cr(VI) metabolism characteristics, including the growth rate, the Cr(VI) tolerance, the removal, absorption and efflux capacity of Cr(VI); ii) Detection the expressions of Cr(VI) resistance-related genes (chrA and chrB), and sulfate channel protein-related genes (sbp, cysA, cysU and cysW genes) by RT-qPCR. Results: Exogenous sulfate enhanced the Cr(VI) tolerance and the removal rate of these three engineered Cr(VI)-resistant strains, and promoted their growth rate under Cr(VI) stress, while suppressed their absorption and efflux capacity. Under a certain sulfate concentration, the Cr(VI) tolerance, removal ability and efflux capacity of these three strains were ranked as follow: eChrAB > eChrA > eChrB, while ranked as eChrB > eChrA > eChrAB for the Cr(VI) absorption rate, respectively. Opposite to the Cr(VI) treatment, exogenous sulfate suppressed the transcription levels of the Cr(VI) resistance-related genes (chrA and chrB) with gradually increased concentrations, and reduced those of sulfate channel protein related genes (sbp,cysA, cysU and cysW) under the medium and high concentrations. Conclusion: Sulfate can enhance the Cr(VI) tolerance and growth of Cr(VI)-resistant strains, via inhibiting the Cr(VI) absorption and efflux in a concentration-dependent manner. The underlying mode of action might be the competition of transport channels between sulfate and Cr(VI), and the suppression of sulfate channel protein related genes expressions by exogenous sulfate. Our results demonstrated an appropriate supplication of exogenous sulfate could contribute to the Cr(VI) pollution management by genes chrA/chrB related Cr(VI)-resistant strains. Additionally, the engineered E. coli strain eChrAB showed more potential for the actual Cr(VI) pollution application than strain eChrA and eChrB.